2016
DOI: 10.1371/journal.pone.0165390
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific D-Dimer Concentration Ranges and Influencing Factors: A Cross-Sectional Study

Abstract: D-dimer level in cancer patients is associated with risk of venous thromboembolism and deep venous thrombosis. Most cancer patients have “abnormal” D-dimer levels based on the current normal reference range. To investigate tumor-specific D-dimer reference range, we compared D-dimer levels for nine different tumour types with healthy controls by using simultaneous quantile regression and constructing a median, 5th percentile, and 95th percentile model of normal tumour D-dimer concentration. Associations with tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
3
23
1
3
Order By: Relevance
“…Although there was a significant difference in OS when patients were stratified according to D-dimer with low D-dimer (<0.7) and high D-dimer (≥0.7) (p = 0.035) in our study, not selected as a predictive factor in multivariate survival analysis. It was reported that H&N cancers have lower metastatic rates and a more favorable prognosis than other malignancies and the D-dimer level was lower than other ones [6]. Our OC cases may correlate with these previous results of lower metastatic rates and a favorable prognosis than other cancers.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although there was a significant difference in OS when patients were stratified according to D-dimer with low D-dimer (<0.7) and high D-dimer (≥0.7) (p = 0.035) in our study, not selected as a predictive factor in multivariate survival analysis. It was reported that H&N cancers have lower metastatic rates and a more favorable prognosis than other malignancies and the D-dimer level was lower than other ones [6]. Our OC cases may correlate with these previous results of lower metastatic rates and a favorable prognosis than other cancers.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the preoperative higher D-dimer values represented a more effective anticoagulation system in patients with free flap success [10]. On the other hand, D-dimer level was independent of gender but was affected by the age of the patient [6]. In our study, there was no significant difference in gender but in age between D-dimer (<0.7 and ≥0.7).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…As Yu et al reported, we could not assess D-dimer status exactly according to normal reference range in the patients with cancers [ 36 ]. Thus, tumor-specific D-dimer reference range should be further investigated with more epidemiological studies and provides a useful standard for clinical practice.…”
Section: Discussionmentioning
confidence: 99%